2021
DOI: 10.1021/acsami.1c00710
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable, Nondestructive, and Simple Visualization of Latent Blood Fingerprints Based on Covalent Bonding Between the Fluorescent Conjugated Polymer and Proteins in Blood

Abstract: Latent blood fingerprints (LBFPs) can provide critical information of foul play and help identify the suspects at violent crime scenes. The current methods for LBFP visualization are still not satisfactory because of the low sensitivity or complicated protocol. This study demonstrates a simple and effective LBFP visualization strategy by integrating a new amphiphilic fluorescent amino-functionalized conjugated polymer with the cotton-pad developing protocol. LBFPs on various substrates are visualized by simply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…Such fluorescence enhancement can be attributed to the increase in absorbance to a small degree, but the main reason should be sweat-induced polymer aggregation, which leads to AIEE behavior. Interestingly, when having blood on the polymer film, the absorption spectrum displayed extremely strong absorbance, coming from blood, which overshaded the absorption of the polymer; and the emission of polymer was significantly quenched; such observation can be explained by the inner filter effect and has been discussed in our previous study focus on blood fingermark development . Even with such a quenching effect, the blood fingermark can still be visualized by the polymer solution since there is some interaction between them, and the adhered polymer can still emit relatively weak fluorescence to give the patterns.…”
Section: Results and Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Such fluorescence enhancement can be attributed to the increase in absorbance to a small degree, but the main reason should be sweat-induced polymer aggregation, which leads to AIEE behavior. Interestingly, when having blood on the polymer film, the absorption spectrum displayed extremely strong absorbance, coming from blood, which overshaded the absorption of the polymer; and the emission of polymer was significantly quenched; such observation can be explained by the inner filter effect and has been discussed in our previous study focus on blood fingermark development . Even with such a quenching effect, the blood fingermark can still be visualized by the polymer solution since there is some interaction between them, and the adhered polymer can still emit relatively weak fluorescence to give the patterns.…”
Section: Results and Discussionmentioning
confidence: 77%
“…Interestingly, when having blood on the polymer film, the absorption spectrum displayed extremely strong absorbance, coming from blood, which overshaded the absorption of the polymer; and the emission of polymer was significantly quenched; such observation can be explained by the inner filter effect and has been discussed in our previous study focus on blood fingermark development. 22 Even with such a quenching effect, the blood fingermark can still be visualized by the polymer solution since there is some interaction between them, and the adhered polymer can still emit relatively weak fluorescence to give the patterns. In summary, the spectral study of the polymer in solid upon different fingermark components further confirmed the AIEE behavior of the polymer induced by sweat during fingermark development.…”
Section: Demonstration Of the Aiee Behavior Of Ptpepe-idamentioning
confidence: 99%
See 1 more Smart Citation
“…This is a fine powder that is applied to a surface with a brush, and it adheres to the oils and sweat left by the suspect’s fingers. The powder will highlight the ridges and valleys of the fingerprint, making it visible to the naked eye or under a magnifying glass. , In this study, the powder of PMD that has the highest fluorescence emission was used for identification of latent fingerprints. As shown in Figure , the hidden fingerprint on a glass surface was dusted by the fine powder of PMD, and the pictures were taken by smartphone after shaking the glasses several times.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] Owing to their poor optical contrast with the substrates, LFPs are invisible to the naked eye and require visualization. 9,10 At crime scenes, LFPs are the most arduous to investigate among the three common types of fingerprints including visible fingerprints, indented fingerprints, and LFPs. [11][12][13] Therefore, two major studies on LFPs are crucial.…”
Section: Introductionmentioning
confidence: 99%